(untitled) (Research, Society and Development, 2021)
This research proposes to contribute, for the use of gamification in the teacher’s practice in higher education in the distance modality, as an active and favorable methodological approach in order to assist the teachers in their actions to transmit knowledge in a clear and efficient way, bringing to the student a meaningful, dynamic, interactive and interesting learning that involves him in the construction of his learning. In the educational scenario, innovating knowledge in the teaching / learning process is what the education system aims for in the new technological context. In this way, it is perceived the lack of teachers regarding the use of active methodologies with different knowledge conditions, making the virtual environment just a content platform. This article aims to produce a study on the main techniques, approaches and tools for the use of gamification in Virtual Learning Environments (VLE) in Higher Education in Distance Education (EAD). The study had a bibliographic search, with exploratory readings, describing the contents in a qualitative way. The reading bases used for the study were Google Scholar, Scielo and Capes open journals. In the data presented, there was an absence of continued training for teachers working in higher education institutions in distance education. Specifically, gamification, with little or almost nothing applied in the practice of teachers, as well, it was realized how much the use of educational game techniques in pedagogical practice in AVA can improve teaching and learning, making teacher and students protagonists in deconstruction and building new knowledge in the face of the new perspective of citizens that the world wants.